1990
DOI: 10.1177/036354659001800504
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of the snapping iliopsoas tendon

Abstract: Eighteen patients with 20 symptomatic hips underwent lengthening of the iliopsoas tendon for persistent painful snapping of this "internal" variety of snapping hip. We referred to the pathologic, painful snapping of the iliopsoas in the deep anterior groin as the "internal" snapping hip. This is in contrast to the more common and better-known "external" snapping that involves the greater trochanter and its overlying soft tissues. The results of our iliopsoas lengthening procedure are presented here. Lengthenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
140
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 9 publications
1
140
0
Order By: Relevance
“…It can be divided into three types: external, internal, and intraarticular, with the external type being by far the most common 1 . The external type is caused by snapping of either the posterior border of the iliotibial band or the anterior border of the gluteus maximus over the greater trochanter [1][2][3][4] . The internal type, which is still the most poorly understood, has a variety of presumed etiologies, with snapping of the iliopsoas tendon over the iliopectineal eminence 5 or over the femoral head 4 being the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be divided into three types: external, internal, and intraarticular, with the external type being by far the most common 1 . The external type is caused by snapping of either the posterior border of the iliotibial band or the anterior border of the gluteus maximus over the greater trochanter [1][2][3][4] . The internal type, which is still the most poorly understood, has a variety of presumed etiologies, with snapping of the iliopsoas tendon over the iliopectineal eminence 5 or over the femoral head 4 being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few reports addressing the internal type of snapping hip [1][2][3][4][5]8 , and none of those reports have dealt exclusively with adolescents. We are aware of only one study in which the authors described a detailed surgical approach and technique for addressing the snapping iliopsoas tendon in patients who were unresponsive to nonoperative measures that C A commentary is available with the electronic versions of this article, on our web site (www.jbjs.org) and on our quarterly CD-ROM (call our subscription department, at 781-449-9780, to order the CD-ROM).…”
Section: Discussionmentioning
confidence: 99%
“…Iliopsoas snapping has received attention in recent orthopedic literature because of positive clinical outcomes of arthroscopic release techniques [93][94][95]. The iliopsoas tendon may snap over the iliopectineal eminence, at the lesser trochanter, or between the iliacus muscle and iliac wing [22,93,96,97], resulting in a palpable or audible snap that may be elicited with movement from the frog-leg position (flexed, abducted, and externally rotated hip) to an extended, internally rotated position [22,41].…”
Section: Snapping Hipmentioning
confidence: 99%
“…MRI also may identify those patients with snapping hips due to ischiofemoral impingement. Conservative management is preferred [41,97], though athletes with continued pain may proceed to ultrasound-guided injection and/or surgical intervention (iliopsoas tenotomy), with nearly all athletes returning to play following surgery [93][94][95].…”
Section: Snapping Hipmentioning
confidence: 99%
“…Open tendon lengthening and arthroscopic tenotomy procedures have been described. Treatment of painful internal snapping hip via arthroscopic release is becoming preferred over open techniques because of the benefits of minimal dissection, the ability to address concomitant intraarticular disorders, and a low complication rate [5,8,9,12]. Numerous authors have reported excellent results with arthroscopic iliopsoas tenotomy at 1 to 2 years postoperatively, with no refractory cases of snapping, minimal to no weakness, and a high prevalence of associated intraarticular disorders that can be managed arthroscopically at the same time [2,3,10,11,21].…”
Section: Introductionmentioning
confidence: 99%